The 2022 FIFA World Cup May Be the Catalyst to Dismantle (or at Least Reform) the Kafala Labor System - Romano, JD Robert J. (Revista Internacional de Pensamiento Político, 2023)
On December 2, 2010, the football/soccer world was stunned when the small Middle Eastern country known as the State of Qatar (Qatar) won the rights to host the 2022 Fédération Internationale de Football Associate (FIFA) Men’s Football World Cup even though its national team had never qualified for a single FIFA World Cup competition. What made Qatar’s bid so attractive to FIFA was that it included  the building of a new airport, a commitment to updating the country’s public transportation infrastructure, the construction of $20 billion worth of new roads and highways which included a bridge to the neighboring country of Bahrain (the longest in the world), the creation of 54 training camps and the opening of a number of hotels to accommodate the spectators, teams, and broadcasting/press corps from the various countries that would be visiting the country over the 29-day contest period. Most importantly, however, Qatar also assured FIFA that it would construct no less than nine football/soccer specific stadiums, each state-of-the-art and equipped with cooling systems that would help alleviate the oppressive Qatari heat since the average temperature on the Gulf peninsula averages around 29 degrees Celsius (85 degrees Fahrenheit) but can reach as high as 45 degrees Celsius (113 degrees Fahrenheit) during the summer months.